Efforts To Improve Student Learning Activities Of 8th Grade Students In SMPN 18 Ambon Through The Implementation Of Think Pair Share Models In Biology Science Learning - Rumahlatu, Paulina W (Sains Global Institut, 2019)
This research is a classroom action research that aims to describe whether there is an increase in the activity of learning biology after the teacher applies a think pair share learning model. The subjects in this study were students of class VIII-A SMPN 18 Ambon with 28 students consisting of 15 male students and 13 female students. The research procedure was a series of stages of research from beginning to end. The design or design in this class action research is a model developed by Stephen Kemmis and Robbin Mc Taggart .. The stages in this study there are four components, namely planning, implementation, observation and reflection. Data in the study were collected through observation sheets, student worksheets, and documentation. From the observations using observation sheets the level of student learning activeness in learning science biology before the action as much as 32% with a low category. In the first cycle the level of student learning activeness with the application of the think pair share model increased to 62.2% in the medium category and in the second cycle increased to 82.6% with a high category.